Community Participation in the Implementation of Development in the South Dampal Subdistrict, Tolitoli Regency - Waris, Irwan; Sakka; Fadryansah (Journal of Public Administration and Government, 2024)
This research aims to describe how community participation in the implementation of development in Soni Village, South Dampal Subdistrict, Tolitoli Regency. This study uses C. Ericson Slamet's theory, which categorizes community participation into three stages: planning, implementation, and supervision. The research employs a qualitative approach with a descriptive research type. Data collection techniques include observation, interviews, documentation, and literature review. The research results indicate that community participation in the implementation of development in Soni Village, South Dampal Subdistrict, Tolitoli Regency is still very low, especially in the stages of implementation and supervision. Factors contributing to this include the community's limited participation in the development process due to specific reasons, prioritizing their individual activities.In the supervision stage, some community members lack awareness to maintain the infrastructure that has been built, resulting in many facilities being neglected. Meanwhile, budget supervision is only carried out by a specific team directly appointed by the community.